Evaluation of silicon nitride as a substrate for culture of PC12 cells: an interfacial model for functional studies in neurons. - Johan Jaime Medina Benavente; Hideo Mogami; Takashi Sakurai; Kazuaki Sawada (PLoS ONE)
Silicon nitride is a biocompatible material that is currently used as an interfacial surface between cells and large-scale integration devices incorporating ion-sensitive field-effect transistor technology. Here, we investigated whether a poly-L-lysine coated silicon nitride surface is suitable for the culture of PC12 cells, which are widely used as a model for neural differentiation, and we characterized their interaction based on cell behavior when seeded on the tested material. The coated surface was first examined in terms of wettability and topography using contact angle measurements and atomic force microscopy and then, conditioned silicon nitride surface was used as the substrate for the study of PC12 cell culture properties. We found that coating silicon nitride with poly-L-lysine increased surface hydrophilicity and that exposing this coated surface to an extracellular aqueous environment gradually decreased its roughness. When PC12 cells were cultured on a coated silicon nitride surface, adhesion and spreading were facilitated, and the cells showed enhanced morphological differentiation compared to those cultured on a plastic culture dish. A bromodeoxyuridine assay demonstrated that, on the coated silicon nitride surface, higher proportions of cells left the cell cycle, remained in a quiescent state and had longer survival times. Therefore, our study of the interaction of the silicon nitride surface with PC12 cells provides important information for the production of devices that need to have optimal cell culture-supporting properties in order to be used in the study of neuronal functions.